Refractory aggregate for molding sand

By using the spherical refractory sintered particles produced by the sintering method, the shape and surface characteristics of the particles are optimized, and the problems of insufficient fluidity and low casting strength of artificial sand in molded sand are solved, thereby achieving better fluidity and high-strength casting molds.

CN119855664APending Publication Date: 2025-04-18ITOCHU CERATECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380064443.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-08-30
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When used as molding sand, existing artificial sand has problems such as insufficient fluidity and low casting strength. Especially in casting mold molds with complex shapes, it is difficult to take into account good flowability and high strength.

Method used

The spherical refractory sintered particles produced by the sintering method are used to ensure that the circularity of the particles is above 0.70, the average particle size is between 0.01 and 1.00 mm, the total volume of pores with a pore diameter of 2 to 10 μm is within the range of 0.20 to 0.50 mL/g, and the turbidity of the amount of fine powder is below 3000 NTU, so as to improve the fluidity of the molded sand and the strength of the casting mold.

Benefits of technology

It effectively improves the fluidity of molding sand and the strength of the mold, and is especially suitable for molding sand aggregates in self-hardening molding and three-dimensional layering molding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005301139150000101
    Figure BDA0005301139150000101
  • Figure BDA0005301139150000121
    Figure BDA0005301139150000121
  • Figure BDA0005301139150000141
    Figure BDA0005301139150000141
Patent Text Reader

Abstract

Provided is a refractory aggregate for molding sand comprising spherical refractory sintered particles artificially manufactured by a sintering method, which is capable of improving the fluidity of molding sand and achieving excellent mold strength. The refractory aggregate for molding sand, which is composed of spherical refractory sintered particles artificially manufactured by a sintering method, has a roundness of 0.70 or more, an average particle diameter of 0.01-1.00 mm, and a total pore volume of 2-10 [mu] m as determined by a mercury intrusion detector within the range of 0.20-0.50 mL / g, and further has a pore diameter of 2-10 [mu] m as determined by a mercury intrusion detector within the range of 0.20-0.50 mL / g. The refractory aggregate for molding sand is configured such that the amount of mixed fine powder is not more than 3000 NTU in terms of a turbidimeter measured by turbidimetry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a refractory aggregate for molding sand, and in particular to the following technology: a refractory aggregate composed of spherical refractory sintered particles artificially manufactured by a sintering method, which can improve the fluidity of the molding sand obtained by using the refractory aggregate and advantageously improve the strength of the casting mold formed by the molding sand. Background Art

[0002] In the past, one of the molds used for casting molten metals such as cast iron, cast steel, aluminum, copper or their alloys is known, which is a mold obtained by mixing or kneading a specified binder, hardener (catalyst) and the like in refractory particles (aggregates) and molding into a target shape. In this mold, as a binder (binder) for bonding refractory aggregates, an organic binder mainly composed of resins such as phenolic resin and furan resin or an inorganic binder mainly composed of water glass, clay, etc. is used. In addition, various molding methods such as wet mold method, air mold method, shell mold method, three-dimensional stacking molding method, etc. are known for molding using this molding sand. By any molding method, a casting mold with a void portion (casting cavity) in the shape of a target casting, especially a self-hardening mold, can be produced.

[0003] On the other hand, as the main body of the molding sand used for the molding of the above-mentioned mold, i.e., refractory particles (aggregates), natural sands such as quartz sand, zircon sand, olivine sand, and chromite sand are widely used. However, naturally produced sands not only have quality deviations such as physical and chemical properties, but also involve depletion problems based on resource reduction in recent years. Therefore, artificially produced refractory particles have been proposed and have been actually used. For example, Japanese Patent Publication No. 3-47943, Japanese Patent Publication No. 4-40095, etc. disclose as a sintering method a method of preparing spherical aggregates by mixing alumina and silica in a prescribed chemical composition to form a raw material composition, granulating into spheres by a method such as a spray dryer, and then sintering the obtained granules in a rotary kiln or the like.

[0004] But, the artificial sand made of the refractory sintered particles made by this sintering method, although its sphericity is good, when burning, the particle surface will produce concavoconvex or particle surface porosity.Therefore, in the casting mold formed by the molding sand modeling formed by adding the binding agent (resin) of a specified amount in this artificial sand, there will be problems such as insufficient strength.And, in order to avoid the problem of this surface state and increase the addition of binding agent, there is the problem of being unable to become fluid sand, that is, the molding sand with good fluidity.Particularly when the molding of casting mold, only relying on the flow characteristics of sand (aggregate) may not necessarily realize the target casting mold, if considering being applied to the actual casting mold, not only the flow characteristics of sand (aggregate) itself, but also the flow characteristics during mixing with resin, hardener, etc. are also very important.

[0005] It can be seen that when sintered sand, which is artificial sand, is used as molding sand, there are problems that need to be solved, namely, improving fluidity and improving the strength of the mold. In particular, when using manual molding methods, injection molding, three-dimensional sand mold stacking molding methods, etc. to make complex-shaped molds, it is required that the molding sand obtained by mixing with a binder maintains good fluidity and the mold made from it has high strength.

[0006] It should be noted that Japanese Patent Publication No. 2006-7319 discloses that the amorphous degree and sphericity of sand particles produced by the flame melting method are limited, so that a casting mold with excellent fluidity, high strength and low thermal expansion can be produced. However, it is difficult to believe that the less uneven the sand surface is, the better the fluidity of the sand is. On the contrary, the less uneven the sand surface is, the thicker the binder (resin) layer that affects the fluidity will be formed, resulting in poor fluidity of the molding sand.

[0007] In addition, Japanese Patent Publication No. 2003-311370 proposes a furan process aggregate, which is used when making a casting mold by mixing furan resin and a hardener in aggregates such as sand and kneading them, and the aggregate has been preliminarily treated to remove fine powder or preliminarily treated to remove alkaline ions. In addition, by using this aggregate, a high-strength casting mold can be molded. However, the document does not disclose at all how the fine powder attached to the surface of the aggregate affects the fluidity of the molding sand formed by mixing with a binder, and further does not disclose how to adjust the surface of the aggregate.

[0008] In addition, regarding the self-hardening flowable mold using artificial sand with a sphericity of 0.8 or more made by a melting method or a flame melting method, in the Japanese Patent Publication No. 2009-119469A, which discloses it, it is pointed out in paragraph

[0006] that although the artificial sand obtained by the sintering method has a good sphericity, there is the following problem: since the sand surface is uneven or the sand surface is porous during firing, the sand cannot obtain sufficient strength if the amount of resin (binder) added is not increased; in addition, if the amount of resin added is increased due to the surface problem, fluidized sand cannot be formed. However, increasing the amount of resin (binder) added due to the increase in the amount of unevenness on the sand surface is unlikely to cause deterioration in fluidity; it is believed that if the amount of resin (binder) added is the same as that of the mold strength, the fluidity is the same regardless of the unevenness on the sand surface. This is probably because it is speculated that the thickness of the binder, etc. present on the sand surface contributes to fluidity and mold strength. If the thickness is roughly the same, the fluidity and mold strength will also be the same.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Publication No. 3-47943

[0012] Patent Document 2: Japanese Patent Publication No. 4-40095

[0013] Patent Document 3: Japanese Patent Application Publication No. 2006-7319

[0014] Patent Document 4: Japanese Patent Application Publication No. 2003-311370

[0015] Patent Document 5: Japanese Patent Application Publication No. 2009-119469 Summary of the invention

[0016] Problem that the invention aims to solve

[0017] The present invention is completed under the above background, and the technical problem to be solved by the present invention is to provide a refractory aggregate for molding sand composed of spherical sintered particles that can exert excellent characteristics. Another technical problem of the present invention is to provide a refractory aggregate for molding sand composed of spherical refractory sintered particles artificially manufactured by a sintering method, which can improve the fluidity of molding sand and achieve excellent mold strength.

[0018] Solutions for solving problems

[0019] In order to solve the above technical problems, the present invention can be appropriately implemented in the various methods listed below, and the various methods described below can be adopted in any combination. It should be noted that the methods or technical features of the present invention are not limited to the contents described below, and should be understood based on the inventive concept embodied in the overall description of the specification.

[0020] In order to solve the above-mentioned problems, the main purpose of the first embodiment of the present invention is a refractory aggregate for molding sand, characterized in that it is a refractory aggregate for molding sand composed of spherical refractory sintered particles artificially manufactured by a sintering method, the refractory sintered particles have a roundness of more than 0.70 and an average particle size of 0.01 to 1.00 mm, and the total volume of pores with a pore size of 2 to 10 μm determined by a mercury intrusion meter is in the range of 0.20 to 0.50 mL / g, and further, the refractory aggregate for molding sand is constituted in a manner such that the amount of fine powder mixed in the refractory sintered particles is less than 3000 NTU according to a turbidity meter measured by a turbidimetric method.

[0021] In addition, a second aspect of the refractory aggregate for molding sand of the present invention is characterized in that the refractory sintered particles have a chemical composition containing 40 to 90% by mass of Al2O3 and 60 to 10% by mass of SiO2.

[0022] The third aspect of the present invention is characterized in that the refractory sintered particles have a chemical composition comprising 60 mass % or more of Al2O3 and 40 mass % or less of SiO2, and the total content of Fe2O3 and TiO2 is 3 mass % or less.

[0023] Furthermore, a fourth aspect of the refractory aggregate for molding sand of the present invention is characterized in that the refractory sintered particles are sintered particles of mullite or mullite-corundum.

[0024] Moreover, a fifth aspect of the present invention is a refractory aggregate for molding sand, characterized in that the circularity is 0.75 or more.

[0025] Furthermore, a sixth aspect of the present invention is characterized in that the total volume of the pores having a pore diameter of 2 to 10 μm is within a range of 0.25 to 0.45 mL / g.

[0026] Moreover, the 7th aspect of the refractory aggregate for molding sand of this invention is comprised so that the amount of the said mixed fine powder may become turbidity of 2000NTU or less, It is characterized by the above-mentioned.

[0027] Moreover, the 8th aspect of the refractory aggregate for molding sand of this invention is used as an aggregate for molding sand for molding a self-hardening mold, It is characterized by the above-mentioned.

[0028] Furthermore, a ninth aspect of the refractory aggregate for molding sand of the present invention is characterized in that it is used as an aggregate for molding sand in a three-dimensional lamination molding method.

[0029] Moreover, a tenth aspect of the present invention is directed to a casting mold obtained by molding using the above-mentioned refractory aggregate for molding sand.

[0030] Effects of the Invention

[0031] By using the refractory aggregate for molding sand of the present invention, the fluidity of the molding sand obtained by mixing or kneading the refractory aggregate with a binder, a hardener, etc. can be effectively improved, and the strength of the mold formed by molding with the molding sand can be further improved.

[0032] Furthermore, the refractory aggregate for molding sand of the present invention can be advantageously used as an aggregate for molding sand used in molding a self-hardening mold or an aggregate for molding sand in a three-dimensional lamination molding method. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a graph showing the relationship between the roundness of various artificial sands obtained in Example 1 and the fluidity or mold strength.

[0034] Figure 2This is a graph showing the relationship between the pore volume with a diameter of 2 to 10 μm and the fluidity or mold strength of various artificial sands obtained in Example 1.

[0035] Figure 3 This is a graph showing the relationship between the turbidity (NTU) of various artificial sands obtained in Example 1 and the fluidity or mold strength. DETAILED DESCRIPTION

[0036] The refractory aggregate for molding sand of the present invention is composed of spherical refractory sintered particles artificially manufactured by a sintering method. As long as the particles are spherical and refractory, any known artificial sintered particles can be used as the object of artificial sand. Specifically, there are sintered sand obtained by granulating by a spray drying method and then firing in a rotary kiln, sintered sand obtained by granulating by a rolling granulation method and then firing in a rotary kiln, etc. In addition, in terms of material, sand made of materials such as sintered mullite and sintered alumina can be used. It should be noted that the spherical refractory particles obtained by this sintering method have fine concave-convex on the particle surface, and the binder components and the like will enter therein. Therefore, in order to improve the fluidity of the molding sand and improve the strength of the mold in the present invention, one of the means is to adjust its surface properties.

[0037] In addition, the spherical refractory sintered particles (aggregates) used as the object of the present invention are preferably expected to have a chemical composition containing more than 40% by mass of Al2O3 (alumina) and less than 60% by mass of SiO2 (silicon dioxide), wherein a chemical composition containing 40 to 90% by mass of Al2O3 and 60 to 10% by mass of SiO2 is preferably used. Here, if the content of the Al2O3 is too small, in other words, if the content of SiO2 is too large, the thermal expansion of the sintered particles becomes large, and it is difficult to be used advantageously as the refractory sintered particles of the present invention. In particular, in the present invention, as the refractory sintered particles, it is preferred to use a composition having the following chemical composition: containing more than 60% by mass of Al2O3 and less than 40% by mass of SiO2, and further the total content of Fe2O3 and TiO2 is less than 3% by mass. It can be seen from this that by limiting the content of Fe2O3 and TiO2, which are impurities, sintered particles with high heat resistance can be obtained. In addition, in the present invention, in the above chemical composition, it is preferred to use refractory sintered particles (aggregates) composed of mullite or mullite-corundum materials. It should be noted that, here, mullite-corundum refers to a state in which the crystal structure of mullite and the crystal structure of corundum coexist or are dispersed in the particles.

[0038] In addition, in the present invention, as the spherical refractory sintered particles, it is advantageous to use refractory sintered particles that have a spherical shape that can be basically recognized as a sphere, and generally have a roundness of 0.70 or more, preferably 0.75 or more, and more preferably 0.80 or more. By using spherical refractory sintered particles having such a roundness, the characteristics of the present invention can be more advantageously exerted.

[0039] Here, the roundness of the refractory sintered particles can be measured by a known method, for example, by a particle shape measuring device manufactured by Microtrac Bel: PartAn SI. The device is composed of a sample cell, a stroboscopic LED, and a high-sensitivity CCD camera. The measuring principle is that while the water is circulated by a pump, a sample (refractory sintered particles) is added, and the water mixed with the sample particles passes through the sample cell disposed between the stroboscopic LED light source and the CCD camera. By performing image analysis on the projected image obtained at this time, the projected area and the maximum Feret diameter of each particle are obtained. Then, based on the obtained maximum Feret diameter and the projected area value, the roundness of each particle is calculated by the following formula.

[0040] Roundness = [4 × projected area (mm 2 )] / [π×{maximum Feret diameter (mm)} 2 ]

[0041] Specifically, 5000 or more sample particles are added, the circularity of each particle is calculated, and then the sum of the circularities obtained is averaged by the number of particles measured, thereby determining the respective circularities (average value).

[0042] In addition, the refractory sintered particles (refractory aggregate) of the present invention have an average particle size of 0.01 to 1.00 mm, and the average particle size is preferably about 0.05 to 0.50 mm, and more preferably about 0.07 to 0.40 mm. If the average particle size of the refractory sintered particles is too small, it will be difficult to handle, resulting in problems such as difficulty in molding the mold; in addition, if the particle size is too large, it will not only be difficult to fully utilize the characteristics of the present invention, but also cause the quality of the cast product to decrease. Here, the average particle size refers to the particle size at the cumulative value of 50% in the particle size distribution obtained by laser diffraction scattering method (D 50 ).

[0043] In addition, in the refractory sintered particles artificially manufactured by sintering method, there are a large number of small holes called micropores, mesopores and macropores with pore sizes from 0.1nm to 1000μm on its particle surface, thereby forming a concavoconvex surface shape. In addition, the physical property of sintered particles is closely related to the properties of these holes. Therefore, in the past, for the evaluation of the concavoconvexity of this particle surface, surface roughness (Ra) was used to evaluate large concavoconvexity and even small concavoconvexity, or even fine concavoconvexity, and porosity (water absorption) was used to evaluate medium concavoconvexity and even small concavoconvexity and fine concavoconvexity. However, these evaluation methods are difficult to fully grasp the physical property of sintered particles, particularly the fluidity of the molding sand obtained by mixing (mixing) with a binder, and the strength of the casting mold formed by this molding sand.

[0044] Therefore, the inventors of the present invention evaluated the asperities on the surface of sintered particles as follows. They evaluated the asperities at any pore size based on the pore volume determined by a mercury porosimeter or a mercury intrusion meter based on the mercury intrusion method. The results showed that the absorption of the binder that affects the fluidity of the molding sand and its coating thickness have almost nothing to do with the presence of large or fine asperities, and that the influence of medium-degree asperities and small asperities within the pore size range of 2 to 10 μm is greater. Therefore, for such asperities with a pore size of 2 to 10 μm, the pore volume (total volume) measured by the mercury intrusion method as described above needs to be within the range of 0.20 to 0.50 mL / g.

[0045] Here, the mercury intrusion method (mercury intrusion instrument) is to apply pressure to mercury to press it into the pores or gaps on the surface of the particles, and calculate the diameter of the pores from the pressure applied at this time. Since the amount of mercury intrusion is the volume of the pores, the pore volume at each pore size can be calculated by changing the pressure. Therefore, the value obtained by accumulating the pore volume at a pore size of 2 to 10 μm is taken as the total pore volume of the pore size of 2 to 10 μm. It should be noted that when the total pore volume of the pore size of 2 to 10 μm is lower than (less than) 0.20 mL / g or higher than (greater than) 0.50 mL / g, as studied later, it will have an adverse effect on the fluidity when making molding sand, the strength of the molded mold, etc. In particular, in the present invention, it is advantageous to use sintered particles whose total pore volume of the pores with a pore size of 2 to 10 μm is in the range of 0.25 to 0.45 mL / g.

[0046] In addition, the spherical refractory sintered particles artificially manufactured by sintering method that constitute the refractory aggregate for molding sand are inevitably mixed with fine powder. When mixing (mixing) a binder, etc. in order to obtain molding sand, the binder, etc. will adhere to the fine powder, which has an adverse effect on the strength of the resulting mold. Therefore, in the present invention, the amount of fine powder mixed in the refractory sintered particles (refractory aggregate) is adjusted in a manner that the turbidity meter measured by the known turbidimetry is less than 3000NTU, preferably less than 2000NTU, and more preferably less than 1000NTU. If refractory sintered particles mixed with the fine powder amount whose turbidity exceeds 3000NTU are used, there are problems such as being difficult to achieve high mold strength.

[0047] It should be noted that, here, the turbidity measured by turbidimetry means that the sample (refractory sintered particles) is uniformly mixed with water, the supernatant is taken after standing, and the scattered light intensity and the transmitted light intensity are compared and calculated, thereby calculating in the form of NTU (nephelometric turbidity unit) value. For example, the portable turbidity meter 2100Q manufactured by HACH Company of the United States (sold by DKK Co., Ltd. of East Asia) can be used for measurement. In addition, by calibrating the obtained turbidity using a formazin standard solution, NTU = FTU [℃ (formazin)] can be obtained.

[0048] In addition, when manufacturing the spherical refractory sintered particles (refractory aggregate for molding sand) of the present invention having the above-mentioned characteristics, a raw material composition prepared by mixing Al2O3 raw material and SiO2 raw material to obtain the above-mentioned chemical composition is adopted, and a method of artificially manufacturing sintered particles having a target roundness and average particle size according to a conventionally known sintering method is adopted. However, in this case, in order to make the total pore volume of the pore size of the present invention being 2 to 10 μm within a specified range, it is necessary to control the concavity and convexity of the particle surface.

[0049] Incidentally, the surface unevenness on the sintered particles is caused by crystallization. For example, refractory particles with mullite (3Al2O3·2SiO2) as the main component generate needle-shaped crystals on the particle surface, and their orientation is random, so convex parts will appear. Therefore, the manufacturing conditions are selected to prevent the growth of the needle-shaped crystals, and the convex parts can be suppressed. Therefore, when manufacturing the above-mentioned mullite-based refractory sintered particles, for example, it is preferred to adopt a method of lowering the firing temperature when the spherical granules of the raw material composition are fired in a rotary kiln, thereby suppressing or preventing the precipitation of mullite crystals. In addition, by performing surface grinding (mechanical grinding) after the firing process or the granulation process, or using inorganic substances such as water glass to implement surface coating to fill the concave parts, the total pore volume of the holes to achieve the target pore size is adjusted.

[0050] In addition, with respect to the amount of fine powder mixed in this refractory aggregate for molding sand (refractory sintered particles), the amount of fine powder mixed in the sintered particles can be controlled by performing a dust collection operation in the granulation process performed after the calcination of the granulated material and changing its dust collection power, thereby enabling the preparation of sintered particles that meet the turbidity specified in the present invention.

[0051] In this way, the refractory aggregate for molding sand of the present invention is advantageously formed in the form of new sand, but it should be understood that as long as the roundness, average particle size, total pore volume with a pore size of 2 to 10 μm and turbidity specified in the present invention are met, even regenerated sand obtained by subjecting recovered sand recovered from the molding process, casting process, etc. to a prescribed regeneration treatment can be used as target sand, thereby bringing out the characteristics of the present invention.

[0052] In addition, for the refractory aggregate for molding sand of the present invention thus obtained, in the same manner as before, a known appropriate binder such as an inorganic binder, an organic binder, a hardener (catalyst), etc. is used for mixing or kneading, and after preparing molding sand, a target casting mold, particularly an inorganic or organic self-hardening mold, is formed according to a conventional molding method such as a wet mold method, an air mold method, a shell mold method, etc., thereby advantageously exerting the characteristics of the present invention. In addition, when used as a refractory aggregate for molding sand in a three-dimensional stacking molding method, the characteristics of the present invention can be more advantageously exerted.

[0053] Example

[0054] Below, show embodiment of the present invention and comparative example, more specifically illustrate the present invention, certainly, the present invention is not subject to any restriction of the record of these embodiment.In addition, it should be understood that, in addition to the following embodiment and the specific description given above, can also carry out various changes, modifications, improvements etc. to the present invention based on the knowledge of those skilled in the art in the scope of not departing from the gist of the present invention.

[0055] [Example 1]

[0056] First, natural sand, molten sand and sintered sand A to H having the chemical composition and average particle size shown in Table 1 below were prepared as refractory aggregates for molding sand. Among them, as natural sand, Wedron Silica sand (made in the United States) was obtained from Hyoya Co., Ltd.; in addition, as molten sand, green beads (manufactured by KINSEI MATEC CO., LTD.) were obtained. In addition, for sintered sands A to H, according to a known sintering method, a raw material composition having the chemical composition shown in Table 1 below was used, spherical granules were formed using a spray dryer, and then sintered in a rotary kiln, and then granulated to obtain each sintered sand. It should be noted that when manufacturing these sintered sands A to H, the sintering temperature is set as shown in Table 1, and the presence or absence of dust collection is selected in the granulation process, thereby changing the dust collection power of each sintered sand one by one, so that the removal amount of fine powder of each sintered sand is different.

[0057] [Table 1]

[0058]

[0059] Next, the roundness, pore volume, mold strength and fluidity of each of these refractory aggregates were measured by the following methods. The obtained results of the roundness, pore volume, mold strength and fluidity are shown in Table 2.

[0060] - Determination of roundness -

[0061] The particle shape measuring device PartAn SI manufactured by Microtrac Bel was used to determine the projected area and maximum Feret's diameter of each particle for each refractory aggregate (particle), and the roundness of each particle was calculated from the obtained maximum Feret's diameter and projected area based on the calculation formula of roundness in this article. Then, the roundness of each of more than 5,000 particles was calculated, and then the sum of the obtained roundness values ​​was averaged by the number of measured particles, thereby respectively determining the roundness (average value), which was used as the roundness of each refractory aggregate.

[0062] - Determination of pore volume -

[0063] Measuring device: Autopore IV9520 (manufactured by Shimadzu Corporation)

[0064] Measuring pressure range: atmospheric pressure ~ 50000psia (345MPa)

[0065] (Low pressure port: ~30psia, high pressure port: 30~50000psia)

[0066] Sample weight: about 1.5g

[0067] After filling a specified container with about 1.5 g of the sample, mercury is pressed into the container. The mercury pressure is gradually increased from atmospheric pressure, and the pressure and the amount of mercury pressed in are measured. Then, the diameter of the pores in the sample particles is calculated based on the mercury pressure using the following formula.

[0068] d=-4σ(cosθ) / P

[0069] [It is assumed that the shape of the pore is a cylinder with a diameter of d (m), the surface tension of mercury is σ (N / m), the contact angle between mercury and the sample particles is θ (°), and the pressure applied to mercury is P (Pa)]

[0070] In addition, since the amount of mercury intrusion is the volume of the pores, the pore volume at each pore diameter can be calculated by changing the pressure. Then, the pore volume at pore diameters: 2 to 10 μm is accumulated to obtain the total pore volume of pore diameters 2 to 10 μm, and the value obtained by accumulating the pore volume of pore diameters greater than 10 μm is taken as the total pore volume of pore diameters greater than 10 μm.

[0071] -Determination of mold strength-

[0072] First, with respect to 100 parts by mass of refractory aggregate, a first component including a phenol formaldehyde resin (ISOCURE Part I 330T manufactured by ASK CHEMICALS) which is a cold box resin and a second component (ISOCURE Part II 630T manufactured by ASK CHEMICALS) which is a polyisocyanate are respectively mixed at a ratio of 0.6 parts by mass and kneaded to obtain kneaded sand (molding sand), and the kneaded sand is filled into a mold of 30 mm×10 mm×85 mm by blowing, and then triethylamine which is a tertiary amine catalyst is blown into the mold to solidify the filled molding sand, thereby preparing a target casting mold (test piece).

[0073] Next, the prepared casting mold (test piece) was kept at a temperature of 25°C and a humidity of 55% RH for 24 hours, and then the bending strength (kg / cm2) was measured using an autograph (manufactured by Shimadzu Corporation, AUTOGRAPH AG-X plus 20 kN) under the conditions of a span of 50 mm and a descending speed of 5 mm / min. 2 ).

[0074] -Liquidity Evaluation-

[0075] Water in a ratio of 0.1% by mass was added to each refractory aggregate and kneaded to prepare a mixed sand, which was used to perform a fluidity (tap flow) evaluation test according to JIS-R-2521 (1995). Specifically, the mixed sand to be measured was placed in a cylindrical flow cone with an upper diameter of 37 mm, a lower diameter of 88 mm, and a height of 74 mm, and then the flow cone was taken out, and the maximum diameter of the crushed mixed sand and the diameter in the vertical direction thereof were measured after 5 drop movements from a height of 12 mm using a flow table, and the average value was used as the flow value as the fluidity index of the mixed sand. The larger the flow value, the better the fluidity.

[0076] [Table 2]

[0077]

[0078] According to the results in Table 2, the relationship between the roundness of each refractory aggregate and its fluidity and mold strength is plotted. The results are as follows: Figure 1 As shown, the smaller the roundness value (non-rounded), in other words, the particles are not spherical, the better the fluidity tends to be (see the area surrounded by the solid long ellipse in the figure). It is believed that this is because the smaller the roundness, the less the amount of water that affects the flow (the thickness of water on the sand surface) is. Sintered sands A to H have a smaller roundness than molten sand and show good fluidity. On the other hand, natural sand is believed to have low fluidity. It is believed that the reason is that natural sand has a sharp shape and a small roundness.

[0079] In addition, regarding the mold strength, it was confirmed that the smaller the roundness of the refractory aggregate, the lower the mold strength (see Figure 1 The area surrounded by the long dotted ellipse). As with the above-mentioned effect on fluidity, it is believed that this is because the roundness of the refractory aggregate is small, in other words, when it is non-circular, the surface area of ​​the refractory aggregate increases, and the amount of binder effective in reflecting the mold strength decreases.

[0080] From the above results, it can be seen that in order to obtain good fluidity and high mold strength, it is necessary to use refractory aggregate with a roundness of 0.70 or more.

[0081] In addition, the relationship between the total pore volume of each refractory aggregate of diameter 2 to 10 μm and fluidity and mold strength in Table 1 is plotted. Figure 2 .from Figure 2It can be seen that the more (larger) the total pore volume of pores with a diameter of 2 to 10 μm, the better the fluidity (see the solid line in the figure). This is believed to be because the more total pore volume, the more water enters the pores, so the amount of water that affects the flow (the thickness of water on the sand surface) decreases. Sintered sands A to H used as refractory aggregates all show good fluidity, while the fluidity value of molten sand is lower. This is believed to be because the pore volume of molten sand is very small, resulting in a thicker water thickness on the sand surface.

[0082] Therefore, it is considered that in order to obtain good fluidity of the molding sand, the total volume of pores having a diameter of 2 to 10 μm in the refractory aggregate (total pore volume) needs to be 0.20 mL / g or more.

[0083] In addition, about Figure 2 As shown in the figure, the relationship between the total pore volume of 2 to 10 μm in diameter increases, and the mold strength tends to decrease as shown by the dotted line. In particular, it is confirmed that the mold strength obtained using sintered sand A is low. As the reason for the decrease in mold strength, it is believed that when the total pore volume increases, the binder enters the concavo-convex surface of the refractory aggregate, thereby reducing the amount of binder effective for reflecting the mold strength.

[0084] Therefore, in order to obtain high mold strength, it is considered effective that the total volume of pores having a diameter of 2 to 10 μm in the sintered sand is 0.50 mL / g or less.

[0085] It should be noted that the above Table 2 also shows the measurement results of the total volume of pores with a diameter greater than 10 μm. However, when studying the relationship between the total pore volume with a diameter greater than 10 μm and the fluidity and mold strength, it was found that, unlike the relationship between the total pore volume with a diameter of 2 to 10 μm and the fluidity and mold strength, the total pore volume with a diameter greater than 10 μm has almost no benefit on fluidity and mold strength.

[0086] From the above results, it is understood that in order to obtain good fluidity and high mold strength, it is necessary to use a refractory aggregate having a total volume of pores with a diameter of 2 to 10 μm in the range of 0.20 to 0.50 mL / g.

[0087] Here, in order to understand the amount of residual fine powder in each of the sintered sands A to H used as refractory aggregates, the turbidity was measured by the following turbidimetric method, and the results are shown in the following Table 3 together with the fluidity and mold strength shown in Table 2 obtained above.

[0088] -Determination of turbidity-

[0089] After 20g of refractory aggregate and 50mL of water as the measurement object were stirred and mixed with a stirrer for 30 minutes, the supernatant was left to stand for 30 minutes to obtain the supernatant. The supernatant was used to obtain the turbidity (NTU) using a turbidimeter (made by HACH, USA, portable turbidimeter 2100Q, and sold by DKK Co., Ltd., East Asia) using a 90° scattered light / transmitted light ratio determination method (transmission scattering method). It should be noted that the smaller the value of the turbidity (NTU), the less the amount of mixed fine powder.

[0090] [Table 3]

[0091]

[0092] In addition, the relationship between the turbidity, fluidity and mold strength of each sintered sand shown in Table 3 is as follows: Figure 3 As shown by Figure 3 As shown by the solid line, the higher the turbidity (NTU), the better the fluidity of sintered sands A to H. This is considered to be because the higher the turbidity, the more fine powder remains in the sintered sand, and the more water adheres to the increased fine powder, so the amount of water that affects the flow (the thickness of water on the sand surface) decreases.

[0093] On the other hand, as the turbidity increases, the mold strength decreases, and the sintered sand A shows a particularly low value. This is because when the turbidity is high and the amount of residual fine powder increases, the binder adheres to the fine powder on the surface of the sintered sand, and the amount of binder effective for achieving mold strength decreases.

[0094] As described above, regarding the turbidity corresponding to the amount of fine powder mixed in the sintered sand, it is important that the turbidity be 3000 NTU or less in order to achieve good fluidity and high mold strength.

[0095] [Example 2]

[0096] As in the above-mentioned Example 1, sintered sands I to O and molten sands having the chemical compositions and average particle sizes shown in the following Table 4 were prepared as refractory aggregates for molding sand. The molten sands were the same as those prepared in Example 1, and sintered sands I to O were each formed into finer sintered sands by the same sintering method as in Example 1. In addition, in the sintering process, the sintering temperature was set as shown in Table 4, and in the granulation process, the presence or absence of dust collection was selected, and the dust collection power of each sintered sand was changed one by one, so that the amount of fine powder removed from each sintered sand was different.

[0097] [Table 4]

[0098]

[0099] Next, the circularity, total pore volume, mold strength and fluidity of each of these refractory aggregates were measured in the same manner as in Example 1. The obtained results of circularity, total pore volume, mold strength and fluidity are shown in Table 5 below.

[0100] It should be noted that furan resin was used as a binder to prepare a test piece (casting mold) for measuring the strength of the casting mold. Specifically, 0.2% by mass of a hardener (Kao-Quaker, C-17) was added to the refractory aggregate and kneaded, and then 1.0% by mass of a furan resin (Kao-Quaker, EF-5301) was added and further kneaded to obtain a kneaded sand. The obtained kneaded sand was then filled into a 50mmφ×50mmH wooden frame, and after hardening, it was kept in an environment of temperature: 30°C and humidity: 80%RH for 24 hours, and then the compressive strength was measured using an automatic plotter in the same manner as in Example 1.

[0101] Regarding the evaluation of fluidity, the flow index value was determined in the same manner as in Example 1 using kneaded sand obtained by adding 0.2 mass % of a hardener (Kao-Quaker C-17) to the refractory aggregate and kneading the mixture.

[0102] [Table 5]

[0103]

[0104] As can be seen from the results in Table 5, in fine-grained sintered sand, the more surface irregularities (total pore volume with a diameter of 2 to 10 μm), the higher the fluidity (flow index value). In addition, in terms of mold strength using furan resin, the more surface irregularities there are, the lower the furan strength tends to be. In particular, sintered sand I, which has a large total pore volume (0.61 mL / g), shows high fluidity, but a low value of mold strength (furan).

[0105] From this, it can be seen that even when furan resin is used, the mold strength shows the same tendency as in Example 1. It should be noted that furan resin is widely used in the preparation of molds, and can be used not only for manual molding using wooden molds, but also for three-dimensional sand mold stacking molding using a 3D molding machine. In addition, in the three-dimensional sand mold stacking molding method, the mold is prepared by re-coating the mixed sand obtained by mixing refractory aggregate and hardener, for example, by vibration, and then dripping furan resin only at the target molding position. In addition, after the furan resin is dripped, the molded mold is different from the manual compaction molding method, and the mold strength is easily reduced. Therefore, when taking out the mold prepared by stacking molding, a moderate mold strength is required to be able to withstand the vibration and transportation during removal, and generally a mold strength of 10kg / cm 2In addition, when making a mold with a complex shape, fine-grained molding sand with a median particle size of about 0.11mm to 0.13mm is widely used from the perspective of mold surface roughness. Therefore, in the three-dimensional sand mold stacking molding method, fine-grained refractory aggregates are required to have higher fluidity and high mold strength.

[0106] As can be seen from the results in Table 5 above, the mold strength obtained by using furan resin in fine-grained sintered sand is also highly correlated with the pore volume. Therefore, not only in the manual molding method but also in the three-dimensional sand mold stacking molding method, by using sintered sand with a limited pore volume (0.20 to 0.50 mL / g), a good mold that maintains good fluidity and has high mold strength can be produced. In particular, sintered sand J has a furan strength of 13.1 kg / cm while maintaining high fluidity. 2 , which has sufficient mold strength for the three-dimensional sand mold stacking molding method. In contrast, the surface of the molten sand is relatively low in unevenness, so even compared with the coarse-grained sand of Example 1, the fluidity is significantly lower. It can be seen from this that the molten sand lacks fluidity in the three-dimensional sand mold stacking molding method and is not suitable for sand mold molding.

[0107] In addition, in order to understand the amount of fine powder remaining in each of the sintered sands I to O and the molten sand, the turbidity was measured by turbidimetry in the same manner as in Example 1, and the results are shown in Table 6 below together with the fluidity and mold strength obtained above.

[0108] [Table 6]

[0109]

[0110] As can be seen from the results in Table 6, in sintered sands I to O, the higher the turbidity, the higher the fluidity, while the mold strength of the mold using furan resin as the binder resin decreased, showing the same results as in Example 1. In particular, sintered sand J has a turbidity of 2780 NTU and a furan strength of 13.1 kg / cm while maintaining high fluidity. 2 This indicates that the mold has sufficient strength for the three-dimensional sand mold stacking method. In addition, although the turbidity of sintered sand O is low, it shows fluidity that can be used in the three-dimensional sand mold stacking method, while the fluidity of molten sand is significantly lower than that of sintered sand. This is because there is a moderate pore volume on the sand surface of sintered sand, and the amount of hardener entering the pore volume increases, thereby reducing the amount of hardener that affects the flow (the thickness of the hardener on the sand surface), showing good fluidity; while in molten sand, there is less pore volume on the sand surface, and compared with sintered sand, the amount of hardener that affects the flow is more, thereby significantly reducing the fluidity.

Claims

1. A refractory aggregate for molding sand, characterized in that: It is composed of spherical refractory sintered particles artificially produced by sintering. The refractory sintered particles have a roundness of more than 0.70 and an average particle size of 0.01 to 1.00 mm, and the total volume of pores with a pore size of 2 to 10 μm determined by a mercury intrusion meter is in the range of 0.20 to 0.50 mL / g. Furthermore, the refractory aggregate for molding sand is constituted in such a way that the amount of fine powder mixed in the refractory sintered particles is less than 3000 NTU according to a turbidity meter measured by a turbidimetric method.

2. The refractory aggregate for molding sand according to claim 1, characterized in that: The refractory sintered particles have a chemical composition including 40 to 90 mass % of Al2O3 and 60 to 10 mass % of SiO2.

3. The refractory aggregate for molding sand according to claim 1, characterized in that: The refractory sintered particles have a chemical composition comprising 60 mass % or more of Al2O3 and 40 mass % or less of SiO2, and the total content of Fe2O3 and TiO2 is 3 mass % or less.

4. The refractory aggregate for molding sand according to claim 1, characterized in that: The refractory sintered particles are sintered particles of mullite or mullite-corundum.

5. The refractory aggregate for molding sand according to claim 1, characterized in that: The roundness is greater than 0.

75.

6. The refractory aggregate for molding sand according to claim 1, characterized in that: The total volume of the pores with a pore diameter of 2 to 10 μm is in the range of 0.25 to 0.45 mL / g.

7. The refractory aggregate for molding sand according to claim 1, characterized in that: The mixture is configured so that the amount of the mixed fine powder has a turbidity of 2000 NTU or less.

8. The refractory aggregate for molding sand according to any one of claims 1 to 7, characterized in that It is used as an aggregate for molding sand for molding a self-hardening mold.

9. The refractory aggregate for molding sand according to any one of claims 1 to 7, characterized in that It is used as aggregate for molding sand in the three-dimensional layered molding method.

10. A casting mold obtained by molding using the refractory aggregate for molding sand according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Production of molding material for casting

    JP1991047943B2

  • Production of spheroidal molding sand

    JP1992040095B2

  • Aggregate for furan process

    JP2003311370A

  • Casting sand

    JP2006007319A

  • Fluid sand self-curing mold

    JP2009119469A